Raw Material Procurement Process In Autoparts Company - Ali Mukmin, Sofyan (International Publisher, 2022)
The purpose of this study was to determine the process of procuring raw materials at the Autoparts company, to find out the obstacles faced in the process of procuring raw materials at the Autoparts company, and to find out the solutions that were carried out to overcome the obstacles in the process of procuring raw materials at the Autoparts company. The research methodology used is descriptive qualitative which aims to describe the conditions and analyze the production administration process at the Autoparts company. In this study, data related to the author's study are sourced from literature studies, field studies, documentation techniques. The results of the research on the Raw Material Procurement Process at the Autoparts Company are as follows: The raw material procurement process at the Autoparts Company is the user submits the procurement of raw materials. Then the specifications are reviewed by PPIC. After that, the user makes a Purchase Request (PR) and submits it to PPIC for signature. Then, the approved Purchase Request (PR) is submitted to the Purchasing section for a Purchase Order (PO). After that, submit the PO to the supplier for ordering raw materials. Then, the supplier sends the raw materials to the warehouse and is received by the warehouse. After that, the warehouse informs the arrival of raw materials to the user. Barriers found in the process of procuring these raw materials. First, there is a discrepancy between the requested raw materials and the actual condition of the raw materials sent. Second, there is unclear information from the supplier regarding the arrival of raw materials to the company. Third, there is damage to the forklift vehicle which is a means of transporting raw materials to the production area. The solutions to the obstacles that occur. First, before the purchase request is submitted to the purchasing department, the user checks again so that there is no incomplete raw material specification data. Second, the company asks the supplier for confirmation regarding the departure time and estimated arrival of the requested raw materials. The third, borrowing a forklift from another part that is not in use.